2019
DOI: 10.1002/ange.201901384
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Intrinsic Catalytic Activities of Single‐Gold‐Nanoparticle‐Based Enzyme Mimetics

Abstract: Gold nanoparticles (AuNPs) have been demonstrated to serve as effective nanomaterial-based enzyme mimetics (nanozymes) for an umber of enzymatic reactions under mild conditions.T he intrinsic glucose oxidase and peroxidase activities of single AuNPs and Ag-Au nanohybrids, respectively,w ere investigated by single NP collision electrochemical measurements.Asignificantly high turnover number of nanozymes was obtained from individual catalytic events compared with the results from the classical, ensembleaveraged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 59 publications
(128 reference statements)
1
17
0
Order By: Relevance
“…[11] GNPs possess intrinsic oxidase properties because hydroxide peroxide (H 2 O 2 ) can be generated with the proper physiological components, [12] but the peroxidase properties of GNPs synthesized with phenols (pGNPs) have not been observed from particles with a large size (>20 nm) because of the limited active sites. [13,14] Since ROS decomposed from H 2 O 2 by peroxidase is more lethal to bacteria, it is desirable to produce peroxidase-like properties on pGNPs to promote antibacterial efficiency. It has been observed that the active catechol moiety in phenols provides binding sites for ions such as Fe and the Fenton reaction produces ROS in the presence of H 2 O 2 .…”
mentioning
confidence: 99%
“…[11] GNPs possess intrinsic oxidase properties because hydroxide peroxide (H 2 O 2 ) can be generated with the proper physiological components, [12] but the peroxidase properties of GNPs synthesized with phenols (pGNPs) have not been observed from particles with a large size (>20 nm) because of the limited active sites. [13,14] Since ROS decomposed from H 2 O 2 by peroxidase is more lethal to bacteria, it is desirable to produce peroxidase-like properties on pGNPs to promote antibacterial efficiency. It has been observed that the active catechol moiety in phenols provides binding sites for ions such as Fe and the Fenton reaction produces ROS in the presence of H 2 O 2 .…”
mentioning
confidence: 99%
“…Although the metallic GOx-like NPs yielded >99% gluconic acid, these materials suffered from high adsorption of reaction products resulting in their oxidation and inactivation [212]. The most extensively studied nanooxidases used for selective oxidation of glucose to gluconic acid are AuNPs [4,210,[213][214][215][216][217][218][219][220][221][222] (see Table 8). Gold NPs are much more resistant to O 2 compared with Pt and PdNPs and their reaction products have a lower affinity to adsorption onto the Au surface, in addition to being more active and selective under mild conditions [212].…”
Section: Nanooxidasesmentioning
confidence: 99%
“…They are named "tandem NZs" (nanomaterials with tandem enzyme-like characteristics). Ma and coauthors [222] investigated catalytic properties of single AuNPs and Ag-Au hybrid NPs as possible GOx and PO mimetics. The electrochemical experiments demonstrated that a high turnover of NZs was obtained from individual catalytic elements compared to results from ensemble-averaged measurements as a classic approach.…”
Section: Nanooxidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The key issue is the signal-to-noise ratio determined by the background current in circuit or interference from chemical species. Many efforts have been made to resolve the current at lower ranges, such as ultramicroelectrodes 19,20 and surface-enhanced Raman spectroscopy 21,22 ; however, the detection limit is normally restricted in the picoampere to nanoampere range 13,15 . It is highly desirable to develop a new electrochemical detection strategy avoiding above interferences.…”
Section: Introductionmentioning
confidence: 99%